Bernardi Integral Operator and Its Application to the Fourth Hankel Determinant. (9th September 2022) - Khan, Abid; Haq, Mirajul; Cotîrlă, Luminiţa-Ioana; Oros, Georgia Irina
Abstract : In recent years, the theory of operators got the attention of many authors due to its applications in different fields of sciences and engineering. In this paper, making use of the Bernardi integral operator, we define a new class of starlike functions associated with the sine functions. For our new function class, extended Bernardi's theorem is studied, and the upper bounds for the fourth Hankel determinant are determined.